Vertical head impulse and caloric are complementary but react opposite to Meniere's disease hydrops. (4th December 2018) - Fukushima, Munehisa; Oya, Ryohei; Nozaki, Kengo; Eguchi, Hirotaka; Akahani, Shiro; Inohara, Hidenori; Takeda, Noriaki
Abstract : Objectives/Hypothesis: Meniere's disease (MD) patients can show normal head impulses despite poor caloric test results. This study aimed to investigate the discrepancy in the vestibulo‐ocular reflex (VOR) in MD patients and whether endolymphatic hydrops (EH) influence the VOR. Study Design: Prospective, cross‐sectional observational study. Methods: Ninety MD patients were enrolled. Neuro‐otological testing, including a video head impulse test (vHIT) of all semicircular canals (SCs), and gadolinium‐enhanced inner ear magnetic resonance imaging were performed. The vestibular EH volume was quantitatively evaluated by processing magnetic resonance images. Results: Abnormal vHIT results in MD patients were found most frequently in the posterior (44.4%) SCs, followed by the horizontal (13.3%) and anterior (10%) SCs. Canal paresis (CP) was assessed using the vHIT and the caloric test, and results were not significant when vHIT responses were assessed as CP only using the horizontal SC. The difference in the vestibular EH between the presence and absence of CP was not significant if assessed using the vHIT ( P = .5591), but it was statistically different if assessed using the caloric test ( P = .0467). Conclusions: The contradictory reaction of VOR in MD patients may result from the high specificity but low sensitivity of CP in the horizontal vHIT. EH volume in the vestibule affects the caloric response but does not affect the vHIT response. Level of Evidence: 2b Laryngoscope, 129:1660–1666, 2019